2021
DOI: 10.3390/cancers13040747
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Impact of Alpha-Fetoprotein and Tumor Burden on Long-Term Outcomes Following Curative-Intent Resection of Hepatocellular Carcinoma

Abstract: Introduction: The prognostic role of tumor burden score (TBS) relative to pre-operative α -fetoprotein (AFP) levels among patients undergoing curative-intent resection of HCC has not been examined. Methods: Patients who underwent curative-intent resection of HCC between 2000 and 2017 were identified from a multi-institutional database. The impact of TBS on overall survival (OS) and cumulative recurrence relative to serum AFP levels was assessed. Results: Among 898 patients, 233 (25.9%) patients had low TBS, 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The present study validated the prognostic utility of preoperative serum CA19-9 and suggested that elevated CA19-9 level correlated to worse OS and RFS in ICC patients after curative resection. Incorporating tumor-specific biomarkers to prognostic index may improve the predictive accuracy and maximize clinical benefit by optimization of patient selection for surgical resection ( 33 ). Qiu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The present study validated the prognostic utility of preoperative serum CA19-9 and suggested that elevated CA19-9 level correlated to worse OS and RFS in ICC patients after curative resection. Incorporating tumor-specific biomarkers to prognostic index may improve the predictive accuracy and maximize clinical benefit by optimization of patient selection for surgical resection ( 33 ). Qiu et al.…”
Section: Discussionmentioning
confidence: 99%
“…According to current studies ( 23 ), prediction models including serum AFP can enhance the predicting recurrence of tumor after liver transplantation. Consequently, some surgeons will choose AFP models to select HCC patients who may not match Milan transplantation criteria ( 24 ). In addition, researchers are working on constructing a predictive model including AFP for HCC that involves Child B liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Both TBS and AFP are strong prognosis factors in patients diagnosed with HCC and the fact that these variables are in relation to one another allows the clinician to create a stronger prediction regarding the possible outcome. Notably, literature data demonstrated that TBS and AFP have a synergistic impact on outcomes in these patients [ 22 ]. Moreover, in a recent study conducted by Tsilimigras [ 22 ], patients with similar values of TBS had different evolution, depending on AFP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, literature data demonstrated that TBS and AFP have a synergistic impact on outcomes in these patients [ 22 ]. Moreover, in a recent study conducted by Tsilimigras [ 22 ], patients with similar values of TBS had different evolution, depending on AFP. We did not encounter any association between AFP and tumour burden calculated by SEC.…”
Section: Discussionmentioning
confidence: 99%